(3CTgQ GdGZJjGdGJ aj GdESdGe (B:s (3ef GdbQf GdChd Edi GdbQf GdYGTQ GdgLQj (B/s - (3GdSYjO, NGdO Hf YHO Gddgs ((3HjQhJ (B- (3dHfGf (B:s (3OGQ GdaGQGHj ,s, 2017)
(3jJfGhd gPG GdcJGH CTgQ YedjGJ GdGZJjGdGJ GdJj hbYJ aj GdESdGe, HOAG ef Ref GdNdGaI GdQGTOI, eQhQG HGdYgO GdCehj, hGfJgGA HRhGd GdNdGaI GdYHGSjI aj YGe (B656 (3gLQj(B. (3de jcf eNWWG YfO GdHOA HGdfHT aj OaGJQ GdJGQjN Cf jchf GdcJGH ebJUQG Ydi GdGZJjGdGJ GdSjGSjI, hdcfc SJLO YfO JUaM ChQGb gPG GdYed Cf Ld, Ef de jcf cd GdYedjGJ, bO hbYJ aj SHjd GdJfGaS hGdJMGSO Ydi GdSdWI(B. (3Sha JJaGLC YfO bQGAJc dYedjGJ GdGZJjGd Cf ChGUQ GdbQGHI hGdehOI bO Je GdJaQjW HgG hGdJNdj YfgG ef CLd UYhO GdbeI hJSfe GdYQT(B. (3Sha JUYb YfOeG JLO GdCH jbJd GHfg, hGdGHf jZOQ HCNjg, hGdCe JSee hdOgG, hgcPG(B. s
(3GdZdGa (B: (3aGQS ZUhH(B.s
Keywords: (3GdESdGe hGdGZJjGds -- (3JGQjNs; (3GdJGQjN GdESdGejs -- (3GdYUQ GdYHGSjs; (3JGQjN GdeSdejf s -- (3GdELQGe s -- (3GdGZJjGds